2022
DOI: 10.1111/1556-4029.15176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the (hu)MANid program for sex and ancestry estimation in a diverse, contemporary CT scan‐based sample

Abstract: Human remains from forensic and bioarcheological contexts are often fragmentary, requiring methods for estimating a forensic profile that are based upon limited skeletal features. In 2017, Berg and Keryhercz created an online application, (hu)MANid, that provides sex and ancestry estimation from mandibular morphoscopic traits and linear measurements. In this study, we examine the utility of the (hu)MANid application in a diverse, urban US adult sample (aged 20–45; n = 143) derived from computed tomography (CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…To determine overall accuracy, these were compared to the estimated sex and Native American ancestry. We believe this analytical approach reflects how most practitioners in the field would apply the program and is consistent with the analysis conducted by earlier tests of (hu)MANid (Farhi et al, 2023; Lynch & Cabo‐Perez, 2022).…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…To determine overall accuracy, these were compared to the estimated sex and Native American ancestry. We believe this analytical approach reflects how most practitioners in the field would apply the program and is consistent with the analysis conducted by earlier tests of (hu)MANid (Farhi et al, 2023; Lynch & Cabo‐Perez, 2022).…”
Section: Methodssupporting
confidence: 80%
“…It is important to note that the data from this study comes from dry mandibles, and not CT or 3D scans. To date, research evaluating the utility of the (hu)MANid program has primarily relied on either CT and 3D scans (Farhi et al, 2023; Lynch & Cabo‐Perez, 2022), with Lynch and Cabo‐Perez (2022) including a subset of 41 dry mandibles along with a larger collection of 3D scans. These studies have found the program to have an accuracy lower than that reported by Berg and Kenyhercz (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kranioti et al [44] report an accuracy of 80% based on 2 linear variables in a Greek population. Other reports vary, from around 75% to almost 90%, using univariate or multivariate models [50, 51, 52, 53, 54, 55, 56, 57]. Franklin et al [58] report an exceptionally high accuracy of 95%, but this needs to be interpreted with caution, as 10 variables were applied on a sample of 40 mandibles, suggesting a danger of overfitting.…”
Section: Discussionmentioning
confidence: 99%